ANALISIS FAKTOR MINAT BELAJAR SISWA TERHADAP MATA PELAJARAN MATEMATIKA KELAS XII MAN 4 AGAM - Arni Asih Jelita; Iltavia Iltavia; Gusmali Marnita (KOLONI, 2022)
The purpose of this study was to find out how strong the factors that influence students' interest in learning mathematics in relation to the factors of feeling happy, caring, interested and involved in class XII students of MAN 4 Religion. The research method used is a survey method with a qualitative approach. In this study the techniques used were observation, unstructured interviews and documentation in the form of questionnaires and student learning outcomes. In data processing, this study uses descriptive analysis of the percentage score of the questionnaire. The sample was determined using a random sampling technique. The population used in this study were students of class XII MAN 4 Religion for the 2022/2023 academic year, totaling 38 samples. The results showed that the factors of feelings of pleasure, attention, interest and student involvement were quite high in influencing students' learning interest in learning mathematics. The feeling of pleasure has a percentage score of 22%, the student attention factor has a percentage of 39%, the student interest factor has the highest percentage, namely 26%, and the lowest factor that students have in learning mathematics is 13%. Keywords: Interest in learning, Learning Mathematics, Interest Factor